Health Literacy Management Model for Santri: Digital Thibbun Nabawi Curriculum in the Artificial Intelligence Era - Niken Ristianah; Juni Iswanto (JM-NU: Jurnal Studi Manajemen Pendidikan Islam, 2026)
Background: Health literacy among Indonesian adolescents remains alarmingly low, with 30.7% suffering from stunting, 11.2% experiencing undernutrition, and significant gaps in reproductive and mental health knowledge. Islamic boarding schools (pesantren) house millions of santri yet often lack structured health education curricula. Thibbun Nabawi (Prophetic Medicine) offers a holistic health framework rooted in Islamic teachings, but its integration into pesantren education remains limited and largely non-digital. Meanwhile, Artificial Intelligence (AI) is rapidly transforming education, including in pesantren settings, enabling personalized and adaptive learning. Objective: This study aims to develop a health literacy management model for santri through a digital Thibbun Nabawi curriculum integrated with AI-based learning technologies. Method: This qualitative study employs a grounded theory approach (Corbin & Strauss, 2015). Data were collected through in-depth interviews, participant observation, and document analysis involving pesantren administrators, curriculum developers, Thibbun Nabawi instructors, santri, and educational technology practitioners in selected pesantren in [location]. Data analysis followed the Corbin and Strauss grounded theory procedure. Findings: The study identified three core categories: (1) the urgency of structured health literacy through Thibbun Nabawi in pesantren, (2) the integration of digital platforms and AI in Thibbun Nabawi curriculum delivery, and (3) a four-phase health literacy management model encompassing curriculum design, digital content development, AI-assisted personalized learning, and evaluation. Conclusion: A substantive theory of Digital Thibbun Nabawi Health Literacy Management is proposed, offering a framework for integrating prophetic medicine into pesantren education through AI-enhanced digital learning, addressing the critical gap in adolescent health literacy in faith-based educational settings.